Leveraging Simulation and Virtual Reality for a Long Term Care Facility Service Robot During COVID-19 - Franco dos Reis Alves, Silas; Uribe Quevedo, Alvaro; Chen, Delun; Morris, Jon; Radmard, Sina (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2021)
Providing care to seniors and adults with Developmental Disabilities (DD) presents challenges associated with care, companionship, medication intake, and fall monitoring among others. Currently, measures to prevent the spread of COVID-19 have seen restricted access to those living in long-term care facilities (LTCFs). While technologies such as robotics and virtual reality (VR) have seen advances in overcoming the aforementioned challenges, the restrictions have impacted research and development relying on human participants. Recently, the use of synthetic data for training motion detection algorithms and virtual worlds has been gaining momentum as an alternative continue for simulating robot and human interactions instead of relying on public databases and physical locations. Here, we propose the development of VR robot simulator for Aether™, a socially assistive mobile robot created to help seniors and people living with DD to achieve a higher degree of independence. For example, Aether™ can assist caregivers by alleviating the burden of care by monitoring the LTCF for tripping hazards, open doors and cabinets. Our simulator allows configuring the virtual Aether™ robot to navigate a virtual environment and detect upper limb gestures performed by a virtual avatar. Our preliminary results indicate that the virtual sensor has detection equivalent to the real sensor, thus ensuring that the simulated data is transferable for real-world testing.